Transformasi Demokrasi: Inklusi digital untuk keadilan sosial global - syiham, yasin rahadatul (Maliki Interdisciplinary Journal, 2026)
In the age of technological convergence and global governance, digital inclusion has become a basic requirement for creating a substantial and fair democracy. Differences in access to digital infrastructure—including internet connections, technological capabilities, and device ownership—not only reflect existing economic inequalities, but also systematically reproduce political and social exclusion. This study analyzes the causal relationship between digital inclusion and strengthening democracy in the context of global social justice, by identifying structural mechanisms that support or hinder citizens' equal participation in digital public spaces. Using a multidisciplinary approach that combines deliberative democracy theory, digital political economy, and global development studies, this research analyzes how the digital divide maintains existing power hierarchies and also creates new forms of marginalization—especially for women, indigenous peoples, people with disabilities, and communities in developing countries. Conversely, this research also investigates the transformative potential of digital technology in expanding the space for political participation, increasing government accountability, and mobilizing social movements between countries. The results of this research show that authentic democratic transformation requires more than simply increasing access to technology; This requires changes to digital policies that focus on rights (rights-based approach), strengthening the capacity of local communities, as well as regulations that limit the domination of digital platforms by a number of global actors. Digital inclusion, in this context, is not only a development tool, but also a fundamental aspect of the 21st century project of democratic emancipation.